Comparative transcript profiling of apricot (Prunus armeniaca L.) fruit development and on-tree ripening - Rasori, Angela; Bassi, Daniele; Geuna, Filippo; Ramina, Angelo; Tonutti, Pietro; Bonghi, Claudio; Manganaris, George A. (My University, 2011)
Considering the high degree of sequence conservation within the Rosaceae family and, in particular, among the Prunus species, we employed the first available peach oligonucleotide microarray (μPEACH 1.0) for studying the transcriptomic profile during apricot (cv. ‘Goldrich’) fruit development. Apricot fruits were harvested at three distinct developmental stages, corresponding to immature green (6 weeks before fully ripe stage), mature firm ripe (change of peel colour, 1 week before fully ripe stage) and fully ripe, namely T1, T2 and T3, respectively. When applied to μPEACH1.0, apricot target cDNAs showed significant hybridization with an average of 43% of spotted probes, validating the use of μPEACH1.0 to profile the transcriptome of apricot fruit. Microarray analyses carried out separately on peach (cv. ‘Fantasia’) and apricot fruit to profile transcriptome changes during fruit development showed that 70% of genes had the same expression pattern in both species. Such data indicate that the transcriptome is quite similar in apricot and peach fruit and also highlight the presence of species-specific transcript changes. In apricot, 400 and 74 differentially expressed genes were found during the transition from T1 to T2 and from T2 to T3, respectively. Among these, a considerable number of genes encoding IAA protein in action regulators (Aux/IAA) and heat shock proteins (HSPs) were highly up-regulated at early and late ripening, respectively. Intriguingly, the expression profiles of all considered HSPs and some of IAA protein /IAA genes showed different patterns between apricot and peach during the last stages of on-tree fruit development, suggesting the presence of diverse mechanism regulating ripening in these two close phylogenetically related species.
Keywords: Rosaceae; Auxin; Transcription factors; Heat shock proteins; Comparative gene expression; Microarray; Peach